Opportunities for robotic-assisted surgery in treatment of uterine cancer. Current view on the problem - E. V. Slukhanchuk; A. G. Tyan (Акушерство, гинекология и репродукция, 2021)
Endometrial cancer holdzone of the lead positions in the pattern of female oncological diseases, affecting annually around 300,000 women worldwide. Compared to other cancers of the female reproductive system, this pathology has been extensively investigated by conducting large-scale randomized controlled trials, which proved safety and efficacy of using laparoscopic surgery for such patients. In the last years, robotic-assisted surgery has been actively developed globally, including gynecological oncology. Minimally invasive technologies can reduce the volume of blood loss, shorten hospital stay, lower rate of postoperative complications and shorten rehabilitation period. It is necessary to conduct randomized prospective studies assessing robotic-assisted surgery for treating endometrial cancer, especially due to concerns about postoperative prognosis in cancer patients. In addition, studies on developing clinical guidelines to select proper surgical intervention, including robotic-assisted access for surgeons-oncologists are required.